Luas Kolaps Paru pada Anestesia Umum dengan Penilaian Electrical Impedance Tomography Durasi Kurang dari 2 Jam dan Lebih dari 2 Jam - chandra, Susilo; Nashella, Nazalia; Harijanto, Eddy; , Rahendra (Majalah Anestesia dan Critical Care, 2014)
Anestesia dan pembedahan dapat menyebabkan atelektasis intraoperasi, penurunan volume paru dan atelektasis akan menyebabkan komplikasi paru pascaoperasi. Electrical impedance tomography (EIT) merupakan alat pencitraan noninvasif untuk menilai distribusi ventilasi paru. Tujuan penelitian ini adalah untuk membandingkan luas kolaps paru yang terjadi pada anestesia umum dengan durasi kurang dari 2 jam dan lebih dari 2 jam dengan menggunakan EIT dan algoritma Costa dkk, dengan sebelumnya menghilangkan faktor komorbid dan faktor prediktor yang lain. Penelitian ini merupakan uji klinis prospektif yang dilakukan di RSCM Kirana selama bulan Maret sampai Mei 2013 pada 42 pasien dewasa usia 18–59 tahun, ASA 1–2 dan IMT <30 kg/m2 yang menjalani operasi mata elektif dengan anestesia umum. Pengamatan dilakukan selama operasi dengan menggunakan EIT. Pasien dibagi ke dalam dua kelompok berdasarkan durasi anestesia lebih dari 2 jam dan kurang dari 2 jam. Dilakukan pengukuran variasi tidal regional, volume tidal, peak inspiratori presure ,dan positive end-expiratory pressure. Hasil pengukuran dihitung sesuai algoritme Costa dkk untuk mencari luas kolaps yang terjadi. Pada kelompok anestesia umum dengan durasi lebih dari 2 jam didapatkan luas kolaps 16,83±8,47 % dan pada durasi kurang dari 2 jam didapatkan luas kolaps 16,16±11,93 % (p>0,05). Tidak terdapat perbedaan bermakna antara luas kolaps yang terjadi pada anestesia umum dengan durasi lebih dari 2 jam dan kurang dari 2 jam. Kata kunci: Electrical impedance tomography, kolaps paru, komplikasi paru pascaoperasi Anesthesia and surgery can cause intraoperative atelectasis, whereas decreased lung volume, and atelectasis can lead to postoperative pulmonary complications. Electrical impedance tomography (EIT) is a noninvasive imaging to assess lung distribution of ventilation. The aim of this study was to compare lung collapse in patients without co morbid and other predictor of PPCs that undergone general anesthesia with duration more than 2 hours and less than 2 hours using EIT and Costa algorithm. This study was a prospective clinical trial conducted in RSCM Kirana during March to May 2013 on 42 patients aged 18–59 years, physical status ASA 1–2, and BMI < 30 kg/m2 underwent elective eye surgery under general anesthesia. The EIT was used intraoperatively. At the end of anesthesia, the patients were divided into two groups based on the duration of anesthesia more than 2 hours and less than 2 hours. The regional tidal variation, tidal volume, peak inspiratory pressure, and positive end-expiratory pressure were observed then. Costa algorithm was used to calculate the lung collapse. In duration of anesthesia more than 2 hours group the lung collapse was 16,83 ± 8,47 %. In duration of anesthesia less than 2 hours group the lung collapse was 16,16±11,93 % (p>0,05). There was no significant difference between lung collapse in anesthesia duration more than 2 hours and less than 2 hours group. Key words: Electrical impedance tomography, lung collapse, postoperative pulmonary complications Reference Degani-Costa LH, Faresin SM, Falcao LF. Preoperative evaluation of the patient with pulmonary disease. Brazilian J Anesthesiol. 2014;64:22–34. Hedenstierna G. Respiratory physiology. Dalam:Miller’s Anesthesia, edisi ke-7. Philadelphia: Churchill Livingstone Elsevier: 2010, hlm. 361-89. Tusmana G, Bohm SH, Warner DO, Sprung J. Atelectasis and perioperative pulmonary complications in high-risk patients. Curr Opin Anesthesiol. 2012; 25: 1–10 Pelosi P, Gregoretti C. Perioperative respiratory Complications and the Postoperative qonsequences-atelectasis and risk factors. Euro Crit Care and Emerg Med 2009. Maceiras PR. Peri-Operative Atelectasis andAlveolar Recruitment Manoeuvres. ArchBronconeumol. 2010;46(6):317–324 Scholes RL, Browning L, Sztendur EM, Denehy L. Duration of anesthesia, type of surgery, respiratory co-morbidity, predicted VO2max and smoking predict postoperative pulmonary complications after upper abdominal surgery: an observational study. Austral J f Physiotherapy. 2009;55: 191–8. Sogame LCM, Vidotto MC, Jardim JR, Faresin SM. Incidence and risk factors for postoperative pulmonary complications in elective intracranial surgery. J Neurosurg. 2008 Aug;109(2):222–7. Canet J, Gallart L, Gomar C, Paluzie G, Valles J, Castillo J, dkk. Prediction of Postoperative Pulmonary Complications in a Populationbased Surgical Cohort. Anesthesiology 2010; 113(6):338–50. Talab HF, Zabani IA, Abdelrahman HS, Bukhari WL, Mamoun I, Ashour MA, Sadeq B, Sayed SIE. Intraoperative ventilatory strategies for prevention of pulmonary atelectasis in obese patients undergoinglaparoscopic bariatric surgery. Anesth Analg. 2009; 109 (5): 1511–16. Reinius H, Jonnson L, Gustaffson S, Sundborn M, Duvernoy O, Pelosi P, dkk. Prevention of atelectasis in morbidly obese patients during general anesthesia and paralysis–a computarized tomography study. Anesthesiology. 2009;111:979–87. Costa ELV, Borges JB, Melo A, Sipman FS, Junior CT, Bohm SH dkk. Bedside estimation of recruitable alveolar collapse and hyperdistension by electrical impedancetomography. Intens Care Med. 2009;35:1132–7. Moerer O, Hahn G, Quintel M. Lung impedance measurements to monitor alveolar ventilation. Curr Opin Crit Care. 2011;17:260–7. Blankman P, Gommers D. Lung monitoring at the bedside in mechanically ventilated patients. Curr Opin Crit Care 2012;18: 261–6. Muders T, Luepschen H, Putensen C. Impedance tomography as a new monitoring technique. Curr Opin Crit Care 2010; 16: 269–75. Stoelting RK, Hiller SC. The lungs. Dalam: Penyunting. Brown B, Murphy F. Pharmacology and physiology in anesthetic practice,edisi ke- 4. Philadelphia: Lippincott Williams and Wilkins; 2006, hlm. 771–82. Davison R, Cottle D. The effect of anesthesia on respiratory function. ATOTW. 2010